Real-time leadership : find your winning moves when the stakes are high - Noble, David (Writer on industrial management); Kauffman, Carol (Writer on executive coaching) (Ascent Audio, 2023)
The hardest part of leadership is mastering the inevitable high-risk, high-stakes challenges you will face. Whether you're making a split-second decision when your business is knocked sideways or you're finding the best strategy to navigate business-critical long-term circumstances, how can you be in peak form in those most crucial moments? Leadership coaching legends David Noble and Carol Kauffman show you how with their innovative new framework-MOVE-which equips you with the tactics you need to slow down high-stakes situations before they speed you up. You'll learn to master the moment, generate response options, and quickly evaluate those options before acting. As you get better and better at using the framework, you'll find you can recognize these moments as they arrive, like a great athlete who can read the field as a play unfolds or a great conductor who anticipates what's needed to deliver a great performance. Noble and Kauffman bring decades of experience coaching thousands of leaders, along with a deep base of research, to show why their unique two-on-one coaching method works and how it's done. Real-Time Leadership is a compelling and demystifying look at how the MOVE framework delivered positive results for them-and how it can for you, too.